(untitled) (Global Journal of Science Frontier Research, 2023)
An approach combining reverse-phase high-performance liquid chromatography RP-HPLC and electrospray ionization mass spectrometry ESI-MS was developed to analyze Urushiol congeners in poison ivy extract The peak signatures detected in poison ivy were separated in 18 min at wavelengths 254 nm 260 nm and 280 nm with a gradient elution on the RP-HPLC system The ESI-MS data confirmed the fragmentation patterns of six Urushiol congeners C15 0-2 and C17 1-3 detected in the poison ivy extract Recovery studies conducted with Urushiol 15 2 show recovery within 2 well within the recovery efficiency of 15-20 The validation data showed that the limit of detection LOD and limit of quantitation LOQ for Urushiol 15 2 was 0 29 0 03 ppb and 0 97 0 01 ppb respectively with a sensitivity of 0 110 0 002 mAU ppb-1 A standard addition calibration approach was used to quantify the Urushiol 15 2 content in the poison ivy extract and reveal one poison ivy leaf may contain 0 674 0 025 mg g of Urushiol 15 2 Our investigation demonstrates the quantitation of Urushiol congeners in complex mixtures This same approach can be beneficial for analyzing other chemical components in food and different types of complex matrices